Imprint of overgrazing on the soil and vegetation of fertility islands in the degraded succulent Karoo, South Africa - Saaed, Muniem W.; Jacobs, Shayne M.; Masubelele, Mmoto L.; Samuels, Igshaan M.; Khomo, Lesego (Land degradation & development, 2022)
Islands of fertility (IOF) emerge when vegetation exerts such a considerable influence on soil properties that sub‐canopies become significantly more fertile than inter‐canopies. How confounding phenomena such as grazing patterns, seedbank dynamics and temporal changes impact IOF, has not been thoroughly examined. Soil and vegetation characteristics of 43 IOF in the Tankwa Karoo were surveyed along a rainfall gradient spanning three plant communities. Sixteen were in the Tankwa Karoo (TK) plant community, 14 in the Tankwa Wash (TW) and 13 in the Tankwa Escarpment (TE). The IOF were identified from aerial photos as clumps of shrubs separated by bare patches. Soils were described in 2014 and the seedbank composition in 2014 and 2015. Concentrations of nutrients, carbon and sodium were measured in IOF less than 5 years, 5–15 years and 30 years liberated from livestock grazing. Electrical conductivity, clay, nitrogen and carbon were the only soil properties that were significantly different from IOF to bare patch. The seedbank in IOF was identical to that in the bare patches. There was no significant difference in IOF versus bare patch nutrient concentrations in the three sampling locations. The soil in IOF was richer, more fertile and had a better structure than the soil in bare patches between IOF. There was a sharp turnover in seedbank composition in the two, drought‐ridden years. Longer grazing exclusion did not influence the nutrient concentrations. Findings here suggest that IOF are dynamic in space and time and are essential elements of landscape heterogeneity with critical ecosystem services. They should hence be managed and monitored to sustain them in landscapes to reverse their degradation, despite being the result of degradation.